Analysis of the Effect of Economic Growth, Education Level on Open Unemployment Rates in Sumatera - Kurniawan, Rizky Dwi; Sunoto, Sunoto (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to determine the effect of economic growth and education level on the level of open unemployment in Sumatra. The data used is secondary data, the analysis method used is panel data regression and the model used is random effect. The results obtained are that the Education Level variable has a negative and significant effect on the unemployment rate in Sumatra while Economic Growth has a negative and significant effect on inflation in Sumatra. Based on the results of the analysis, it can be concluded that the Unemployment Rate responds to changes in each variable: Educational Level and Economic Growth.